Penerapan Metode Inferensi Fuzzy Takagi Sugeno-Kang Untuk Prediksi Hasil Panen Kelapa Sawit - Yanto, Budi; Rouza, Erni; Saputra, Edi (Riau Journal Of Computer Science, 2019)
Palm oil is one of the main crops and seeds in Indonesia. In oil palm plantations, oil palm crops are the most important things. Oil palm crops in the right time and quantity are what the farmers want. Therefore, harvest prediction is needed to be used as reference of palm oil harvest target. Determination of harvest targets required a method that is able to predict the yield of oil palm. In this research, built a system of fuzzy inference with TSK method (Takagi Sugeno Kang), which aims to predict the yield of oil palm farmers. The fuzzy rules in the form of IF antecedent THEN are consequent, using consequent linear equations of the input variables. The coefficients of each variable of linear equation are consequently derived based on the expected yield of the harvest. The results of prediction testing of Palm Oil harvest production in 3 seasons, namely Dry Season, Rainy Season, Fertilization, input the number by values of variable with to the given range prove that the fuzzy inference of the TSK method can calculate palm oil crop predictions well.